Can a small city be considered a smart city? - Lopes, Isabel Maria (2018)
The term “smart cities” has been widely used over the last years. The main goal of the smart cities initiative is to enable cities to manage their assets efficiently, investing in innovation and creativity as a way to promote sustainable and inclusive urban development. When tackling such an emerging and promising area, it is important to know whether all cities can be fitted into this concept regardless of their size or location, thus promoting social equity throughout the whole territory. The Portuguese Smart Cities Network includes 46 municipalities throughout the national territory. There are a lower number of such cities located in the interior part of the country. This was one of the reasons leading to this research work aiming to find out whether a small/medium inland city can be considered a smart city. There are a number of measures of action that a city can explore in order to be considered a smart city. Considering the place under study, the aims of this research work are to ascertain what measures are being adopted to increase the efficiency of the city’s resources and services management and to what extent it can be considered a smart city